Low-Carbon Strategic Planning of Integrated Energy Systems - Guo, Yongtao; Xiang, Yue (Frontiers in Energy Research, 2022)
With the rapid promotion of renewable energy technologies and the trend to a low-carbon society, the positive impacts of an integrated energy system that realizes various forms of energy utilizing improvement and carbon reduction have fully emerged. Hydrogen with decarbonized characteristic integrating into the integrated energy system is becoming a viable option to offset the intermittency of renewables and decline the fossil fuel usage. An optimal planning model of wind-photovoltaic-hydrogen-storage integrated energy system with the objective of total economic and environmental costs minimization in consideration of various energy technology investments is proposed. Case studies are developed to compare the economic and environmental benefits of different energy investment scenarios especially hydrogen applications. The cost-benefit analysis is carried out and proved that the hydrogen investment is not a cost-competitive option but can alleviate the burden of carbon emissions somehow. Finally, sensitivity analysis of key parameters of sale capacity, carbon tax and renewable penetration level are performed to indicate the rational investment for a wind-photovoltaic-hydrogen-storage integrated energy system.